53.4: U‐Shaped‐Emitting‐Surface Daytime Running Light Using Customized Light Pipe with Microstructure. Issue 1 (1st July 2013) - Zhang, Jain‐Hong; Chen, Kuan‐Yu; Cheng, Yao‐Chien; Wang, Alex
Abstract: A customized light pipe with microstructure design, which meet aesthetic U‐shaped emitting surface requirement and comply with the regulation (UNECE Regulation No. 87) of automotive daytime running light (DRL) is presented. Compared to the planar light pipe, the central intensity can be increased by 102% by adding sidewall slope and valleys in between LEDs (both act as TIR surfaces); the direct‐viewing uniformity can be highly improved by adjusting LED position and adding microstructure. With 6 LEDs of total 600 lm, the simulated central luminous intensity is 550 cd while the measured value of mock‐up sample is 535 cd, which are in good agreement and both above the ECE R87 standard of 400 cd.